Demographic transition and rural development in Nigeria (2015)
The discourse on population growth has generally given a picture that the increase in the population of any society will negatively affect the utilisation of resources and ultimately overall development. A school of thought gave the impression that the more the population increases, the greater is the poverty, leading to underdevelopment, especially for countries in transition. This argument led to various suggestions and attempts at population control and huge budgetary spending, neglecting positive aspects of population size, particularly in the period of demographic transition, and stressing that growth in population size, especially at certain periods, could not lead to and promote development. But can population growth not be a blessing to growth, especially for the rural areas? This paper was anchored in demographic dividend and labour force models. Utilising some theoretical expositions and drawing from the lessons of countries that have transformed from underdevelopment to developed nations, the paper argued that demographic dividend can be harnessed for the development of especially rural areas in transitional countries like Nigeria. The paper concluded with the submission that, in order to tackle the pervasive poverty in Nigeria, disjointed and inconsistent rural development policies should be jettisoned and the utilization of rural population for the supply of economic goods and services for the overall development of the country embraced